Early kangaroo mother care vs. conventional method in stabilizing low birth weight infant: physiologic parameters (preliminary report) - Rulina Suradi; Piprim B. Yanuarso; Sudigdo Sastroasmoro; Nani Dharmasetiawani (Paediatrica Indonesiana, 2002)
Background Kangaroo mother care (KMC) has been accepted as an effective method in nursing low birth weight infant (LBWI). However, the application of this method in the early life of infants has not been studied in Indonesia.Objective To evaluate some physiologic parameters of LBWI treated with early KMC compared to conventional method.Methods This was a randomized clinical-trial, which compared early KMC to conventional method in stabilizing LBWI in the first 4 hours of life. All LBWI (birth weight 1500-2499 g) bom at Cipto Mangunkusumo Hospital and Budi Kemuliaan Matemity Hospital Jakarta were recruited consecutively in the period of November 2001 until March 2002. The inclusion criteria were spontaneous delivery, APGAR scores 13t and 5th minute 37, and parental consent.Results Sixty-four subjects distributed evenly into early KMC group and control group. One subject in the KMC group and three subjects in the control group were excluded due to respiratory distress. The mean birth weight was 2091 (SO 299.4) g in the KMC group and 2184 (SO 214.9) g inthe control group. The mean gestational-age in both groups was 35.6 (SO 3.0) weeks. There were no statistical differences in mean temperature (P=0.281), heart rate (P=0.956), and respiratory rate (P=0.898) between the two groups during the first 4 hours of life. We found a larger proportion of infants reaching the temperature of 36.5QC in the KMC group, especially at one hour (49% vs. 7%); the difference of proportion was 0.42 (95%CI 0.22 to 0.61).Conclusion Early KMC method is proved to be as safe as conventional method in stabilizing healthy LBWI.